Endovascular management of colic artery pseudoaneurysm: A case report of successful intervention in a 59-year-old male with abdominal hematoma - Shivam Khatri; Rooshi Parikh; Matthew Smith; Joseph Friedman (Radiology Case Reports, 2024)
Visceral artery pseudoaneurysms, including inferior mesenteric artery pseudoaneurysms, are rare, occurring at an estimated incidence of 0.01%-0.2%. The literature reports only around 60 cases of inferior mesenteric pseudoaneurysm to date. The management of this condition lacks a consensus; nevertheless, coil embolization remains the preferred approach for stable patients. Here, we present a unique clinical scenario involving a 59-year-old male who underwent exploratory laparotomy for a retroperitoneal hematoma. Subsequently, he was diagnosed with an inferior mesenteric pseudoaneurysm, specifically affecting the left colic artery, and successfully managed using coil embolization.